The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/children9060914
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Physeal Fractures from the United States National Trauma Data Bank

Abstract: Background: Pediatric long-bone physeal fractures can lead to growth deformities. Previous studies have reported that physeal fractures make up 18–30% of total fractures. This study aimed to characterize physeal fractures with respect to sex, age, anatomic location, and Salter–Harris (SH) classification from a current multicenter national database. Methods: A retrospective cohort study was performed using the 2016 United States National Trauma Data Bank (NTDB). Patients ≤ 18 years of age with a fracture of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…The presentation demographics of physeal fractures and fracture characteristics in the current study were consistent with previous studies. 7,8,[11][12][13][14] Physeal injuries were more common in males in this study cohort, as reported by others. 1,3,7,8,14 The average age of physeal injury to the distal tibia, proximal tibia, and distal femur was 11.3 years, which coincides approximately with the pubertal growth spurt.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The presentation demographics of physeal fractures and fracture characteristics in the current study were consistent with previous studies. 7,8,[11][12][13][14] Physeal injuries were more common in males in this study cohort, as reported by others. 1,3,7,8,14 The average age of physeal injury to the distal tibia, proximal tibia, and distal femur was 11.3 years, which coincides approximately with the pubertal growth spurt.…”
Section: Discussionsupporting
confidence: 88%
“…7,8,[11][12][13][14] Physeal injuries were more common in males in this study cohort, as reported by others. 1,3,7,8,14 The average age of physeal injury to the distal tibia, proximal tibia, and distal femur was 11.3 years, which coincides approximately with the pubertal growth spurt. Kawamoto et al reported the mean ages of injury onset at 10.3 years in boys and 8.9 years in girls, and Peterson et al reported peak ages between 11 and 14 years.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, two general studies provide insight into a broad pediatric fracture population. Fuchs et al [ 22 ] analyzed all physeal long-bone fractures registered in the United States in 2016. Almost 6% of pediatric long-bone fractures involved the physis.…”
mentioning
confidence: 99%